Average Error: 0.0 → 0.0
Time: 7.3s
Precision: 64
$\frac{e^{\left(x + 1\right) + 1} - e^{60}}{2}$
$\frac{e^{1 + \left(x + 1\right)} - e^{60}}{2}$
\frac{e^{\left(x + 1\right) + 1} - e^{60}}{2}
\frac{e^{1 + \left(x + 1\right)} - e^{60}}{2}
double f(double x) {
double r47251509 = x;
double r47251510 = 1.0;
double r47251511 = r47251509 + r47251510;
double r47251512 = r47251511 + r47251510;
double r47251513 = exp(r47251512);
double r47251514 = 60.0;
double r47251515 = exp(r47251514);
double r47251516 = r47251513 - r47251515;
double r47251517 = 2.0;
double r47251518 = r47251516 / r47251517;
return r47251518;
}


double f(double x) {
double r47251519 = 1.0;
double r47251520 = x;
double r47251521 = r47251520 + r47251519;
double r47251522 = r47251519 + r47251521;
double r47251523 = exp(r47251522);
double r47251524 = 60.0;
double r47251525 = exp(r47251524);
double r47251526 = r47251523 - r47251525;
double r47251527 = 2.0;
double r47251528 = r47251526 / r47251527;
return r47251528;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\frac{e^{\left(x + 1\right) + 1} - e^{60}}{2}$
2. Final simplification0.0

$\leadsto \frac{e^{1 + \left(x + 1\right)} - e^{60}}{2}$

# Reproduce

herbie shell --seed 1
(FPCore (x)
:name "(exp(x+1+1)-exp(60))/2"
(/ (- (exp (+ (+ x 1.0) 1.0)) (exp 60.0)) 2.0))